Acute Symptomatic Calcific Discitis Mimicking a Septic Spondylodiscitis - Magda Choueiri; Florent Eymard; Sandra Guignard; Frédéric Pigneur; Xavier Chevalier (Case Reports in Rheumatology)
Acute symptomatic calcific discitis is a poorly understood condition that has been mostly reported in children. Cases in adults have been scarcely reported and may mimic an infectious process. Imaging, including computed tomography, can show the disc calcification but might fail to show it because its resorption can occur early after the onset of symptoms. We report the case of an adult patient presenting with severe cervical-dorsal junction pain, fever, high C-reactive protein (CRP) levels, and imaging findings mimicking an infectious spondylodiscitis, including an erosion of the anterior part of the vertebral endplate. However, the patient improved spontaneously and rapidly, with pain and fever disappearing and C-reactive protein (CRP) returning to normal within a week.